2022
DOI: 10.18618/rep.2022.2.0033
|View full text |Cite
|
Sign up to set email alerts
|

Design and Development of a Multiphase Inverter for Automotive Applications

Abstract: This work describes the development of a multiphase inverter that can operate as a platform for driving and testing electrical machines with up to 15 phases, in addition, it can operate with a fundamental frequency of up to 1 kHz and a switching frequency of 100 kHz. Therefore, a multiphase voltage source inverter (VSI) topology using SiC MOSFETs and approved components for automotive applications was designed and constructed. The developed platform is composed of independent power modules and a control module… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 12 publications
0
3
0
Order By: Relevance
“…Since the magnetic flux density vectors are mainly in the axial direction, due to the yokeless segmented armature, it is possible to use laminated electrical steel with oriented grains in this topology of electrical machine. This special feature of this topology allows obtaining even higher levels of torque per active volume, and higher power and efficiency [12]. The study carried out in this paper uses the prototype of the YASA machine designed in [11].…”
Section: Multiphase Yasa Machinementioning
confidence: 99%
See 2 more Smart Citations
“…Since the magnetic flux density vectors are mainly in the axial direction, due to the yokeless segmented armature, it is possible to use laminated electrical steel with oriented grains in this topology of electrical machine. This special feature of this topology allows obtaining even higher levels of torque per active volume, and higher power and efficiency [12]. The study carried out in this paper uses the prototype of the YASA machine designed in [11].…”
Section: Multiphase Yasa Machinementioning
confidence: 99%
“…It was shown that torque density is improved and torque ripple is reduced with the increase in the number of phases. A following work has developed a multiphase inverter to test multi-star and multiphase electrical machines [12], and the machine designed by [11] was tested with several different electrical connections. It was shown in [12], e.g., that the multiphase machine does not lose synchronization even when one or two phases are open, which demonstrates the faulttolerant characteristic of the multiphase machine.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation